Effects of Price Inflation on Urban Households' Food Expenditure Patterns in Port Harcourt, South-South Nigeria: Insights on Food and Nutrition Security - Michael Ige Ediabai Edaba; Emmanuel Akosim Ebele (Journal of Applied Agricultural Science and Technology, 2025)
Port Harcourt is the most economically vibrant city in Nigeria after Lagos, and it has an estimated population exceeding three million people. In recent years, food commodities, especially energy-rich foods, have continued to gain significant market value in the city. This study examined the effects of price inflation on food expenditure patterns in Port Harcourt, South-South Nigeria, against the backdrop of food and nutrition security. The study examined 265 urban households in the city, and special attention was given to common dietary food sources such as rice, yam, garri, noodles, beans, meat/fish, vegetables, and oils. The research used descriptive and inferential statistical models, including quartile, chi-square, multiple regression, and the Linear Approximate Almost Ideal Demand System models. Results of the analysis revealed that garri and rice were the most frequently consumed food products in the area. Similarly, the households spent a significant weekly share of their food budget (54 per cent) on energy-rich foods (rice, garri, yam, and noodles) compared to meat/fish (46 per percent) and vegetables (27 per cent). Furthermore, in the buildup to the regression analysis. The double-log functional form was selected as the lead equation with an R² of 93.68 per cent, with age (0.1893), household size (0.0512), income (0.0201), price of meat and fish (-0.0081), and consumer preference (0.0038) significantly influencing household expenditure on energy-rich foods. The Marshallian uncompensated own price elasticities for rice, garri, beans, and meat/fish were found to be -0.713, 0.374, -0.891, and -1.271, while the Hicksian cross price elasticities for yam and noodles as well as that of vegetables and oils were 0.062 and 0.163, respectively, implying that these commodities were inelastic and close substitutes. The elasticity estimates indicate that most food commodities are inelastic and exhibit substitution tendencies, particularly between vegetables and oils. Policymakers should therefore prioritize price stabilization, income enhancement, and food supply diversification to strengthen urban food and nutrition security.